The influence of internal marketing on service quality and customer satisfaction in hospitals: literature reviews - Ramadhanty, Nurlaili Maya (Enrichment : Journal of Management, 2023)
This study aims to explore the influence of internal marketing on service quality and customer satisfaction in a hospital environment, with a focus on understanding the related literature. The research method involved a systematic review of academic literature, articles and empirical research related to this topic. Internal marketing is seen as a key factor that can influence the way medical and non-medical personnel interact, work together, and deliver quality service to patients. The results of the literature analysis show that the implementation of an effective internal marketing strategy can improve team collaboration, employee motivation, and a shared understanding of healthcare. In addition, the improvement of service quality in hospitals directly contributes to the level of customer satisfaction. In conclusion, the development of internal marketing in hospitals can significantly affect service quality and, in turn, improve customer satisfaction